UPAYA GURU PEMBIMBING DALAM MENGEMBANGKAN MORAL PESERTA DIDIK DI SMP NEGERI 9 PADANG - Noliza, Noliza; Arief, Asmaiwaty; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The title of this research is effort learning counselor in developing educative by toward student in SMP N 9 Padang. Where in this SMP N 9 Padang. Where Â is found by educative participant which impinge moral, like: impinging moral to teacher and impinge regulation of school. Target of this research is: (1) to know how effort learn counselor in developing moral seen from aspect approach of cultivation of educative by participant value in SMP N 9 Padang, (2) to know how effort learn counselor in developing moral seen from aspect approach of clarification assess educative by participant in SMP 9 Padang. Result of this research lay open that: (1) effort learn counselor in developing moral seen from aspect approach of cultivation of educative by participant value in SMP N 9 Padang reside in at good category that is with percentage 62,59% (2) effort learn counselor in developing moral seen from aspect approach of clarification assess educative by participant in SMP N 9 Padang reside in at good category that is with percentage 63,29%. This research represent out for research to describe about an situation are there. Source of data in this research is educative participant which impinge moral in SMP N 9 Padang amounting to 88 people. Withdrawal of this research sample use Purposive Sampling that is technique determination of sample with certain consideration. Instrument which is used in this research is data colletion tool, while for the analysis of data used by percentage technique. Based on research finding recommended to : (1) counselor teacher and parent to be able to develop educative participant moral, (2) government of Town Padang and On Duty Education of Town Padang to be able to cooperate with counselor teacher and educative by participant parent in SMP N 9 Padang to develop educative participant moral.